Uma ginástica que também se lê: a produção do Compendio de Gymnastica Escolar de Arthur Higgins (1896-1934) - Ana Claudia Avelar (2018)
This work talks about the production of the Compendio de Gymnastica Escolar, by Arthur Higgins, published between the years 1896 and 1934. Arthur Higgins (1860-1934) was a gymnastica teacher at Pedro II Colleges, Normal School, and others institutions in Rio de Janeiro, and also worked in other professional fields. The Compendio de Gymnastica Escolar was analyzed paying attention to its production and its contents, dialoguing with the field of the History of Books and Printed (DARNTON, 1990; CHARTIER, 2002, 2004, 2014; CHOPPIN, 2004). From the places occupied by Arthur Higgins, his networks of sociability are perceived in order to understand his place of writing and publishing of the Compendio . The materiality of the book is also highlighted, in order to understand the Compendio de Gymnastica Escolar e strategies linked to the publication conception, legitimation and dissemination: the printed material is described, the readers targeted and the work publicity elements are presented. The contents of the Compendio were described and compared, trying to perceive changes and continuities between the issues. The use of the Swedish and Belgian gymnasticas methods indications, cited as inspiration by Arthur Higgins are also discussed. The documentary set mobilized was: Compendio editions, the National Library newspapers digital collection; Normal School and Pedro II College institutional documents located in the National Archive and in the Institute of Education of Rio de Janeiro collection. Other documents were also consulted: the Normal School Teaching Programs and the General Fundamentals of Gymnastics books (1834) by Pehr Henrik Ling; and the Gymnastics Teaching Guide for Young People, according to Guillame Docx's official program (1875). When mobilizing this documentary set, it is understood that Arthur Higgins had contact with an intentional writing to attend a readership at the age of sixteen, when he was a journalist in the city of Rio. In addition, the author was present in places that allowed his coexistence with journalists, writers and educators of his time. About the Compendio it is noticed that among the editions there are modifications with the purpose of facilitating the proposed gymnastic exercises teaching, and that these modifications are related to the work of Arthur Higgins as a gymnastica teacher.